Oil‐Fortified Maize Porridge Increases Absorption of Lumefantrine in Children with Uncomplicated Falciparum Malaria. Issue 5 (22nd February 2017) - Mwebaza, Norah; Jerling, Markus; Gustafsson, Lars L.; Silva, Antero V.; Pohanka, Anton; Obua, Celestino; Waako, Paul; Beck, Olof; Homann, Manijeh Vafa; Färnert, Anna; Hellgren, Urban
Abstract: Artemether‐lumefantrine (AL) is a first‐line treatment for uncomplicated malaria. Absorption of lumefantrine (LUM) is fat dependent, and in children, intake is recommended with milk. We investigated whether oil‐fortified maize porridge can be an alternative when milk is not available. In an open‐label pharmacokinetic study, Ugandan children <5 years with uncomplicated Plasmodium falciparum malaria were randomized to receive standard six‐dose AL treatment [one tablet (20 mgA/120 mg LUM) if <15 kg and two tablets if >15 kg] with milk (A) or maize porridge plus oil (B). Parametric two‐sample t ‐test was used to compare relative oral LUM bioavailability. The primary end‐point was LUM exposure till 8 hr after the first dose (AUC0–8 hr ). Secondary outcome included day 7 concentrations (d7LUM ), LUM exposure between days 7 and 28 (AUCd7–28 ) and day 28 PCR‐adjusted parasitological response. Evaluable children (n = 33) included 16 in arm A and 17 in arm B. The AUC0–8 hr was comparable between A and B [geometric mean (95% CI): 6.01 (3.26–11.1) versus 6.26 (4.5–8.43) hr*μg/mL, p = 0.9]. Less interindividual variability in AUC0–8 hr was observed in B ( p = 0.01), but d7LUM and AUCd7–28 were comparable. Children receiving two tablets had significantly higher exposure than those receiving one tablet [median d7LUM (505 versus 289 ng/mL, p = 0.02) and AUCd7–28 (108 versus 41 hr*μg/mL, p = 0.006)]. One parasitological failure (d28 recrudescence) was observed. Our findings suggest that oil‐fortified maize porridge can be an alternative to milk in augmenting absorption of LUM. The lower LUM exposure observed in children dosed with one AL tablet needs further attention.